TINDAK PIDANA PERKOSAAN YANG DILAKUKAN OLEH ANAK DALAM KAJIAN PSIKOLOGI KRIMINAL (Studi Putusan Nomor : 05/Pid.Sus-Anak/2016/PN-Lsm) - Sudana Bambang Suganda; Zulfan Z; Zul Akli (Fakultas Hukum Universitas Malikussaleh, 2022)
Rape is a crime that gets enough attention among the public. In particular, those who commit these crimes are minors, who should play like other children. However, they did an act based on excessive curiosity, so that curiosity resulted in the child being entangled in a rape crime case which was committed because of the curiosity factor. So that researchers are interested in conducting further research with the title